2013
DOI: 10.1016/j.neuroimage.2012.10.051
|View full text |Cite
|
Sign up to set email alerts
|

Three-way (N-way) fusion of brain imaging data based on mCCA+jICA and its application to discriminating schizophrenia

Abstract: Multi-modal fusion is an effective approach to better understand brain diseases. However, most such instances have been limited to pair-wise fusion; because there are often more than two imaging modalities available per subject, there is a need for approaches that can combine multiple datasets optimally. In this paper, we extended our previous two-way fusion model called “multimodal CCA +joint ICA”, to three or N way fusion, that enables robust identification of correspondence among N data types and allows one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
115
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 130 publications
(121 citation statements)
references
References 68 publications
0
115
0
Order By: Relevance
“…Joint independent component analysis (ICA), and linked ICA perform well in spatial decomposition by maximizing the joint independence, but all modalities share a common profile. Combining the strengths of MCCA and jICA, Sui et al developed “MCCA+jICA” [7, 8], a blind fusion algorithm, which successfully captures both multimodal interactions and spatial components at high accuracy to study brain diseases. Other data fusion approaches like independent vector analysis (IVA) generalizes ICA to multiple data sets using the mutual information rate, achieving a similar performance to MCCA+jICA [9].…”
Section: Introductionmentioning
confidence: 99%
“…Joint independent component analysis (ICA), and linked ICA perform well in spatial decomposition by maximizing the joint independence, but all modalities share a common profile. Combining the strengths of MCCA and jICA, Sui et al developed “MCCA+jICA” [7, 8], a blind fusion algorithm, which successfully captures both multimodal interactions and spatial components at high accuracy to study brain diseases. Other data fusion approaches like independent vector analysis (IVA) generalizes ICA to multiple data sets using the mutual information rate, achieving a similar performance to MCCA+jICA [9].…”
Section: Introductionmentioning
confidence: 99%
“…In order to identify the co-altered networks across modalities, we assume that 1) whole brain FNC is a linear mixture of sources in the form of multiple sub-networks (Park et al 2014), 2) whole brain GMD can also be linearly separated into a number of sources as spatial independent components (Xu et al 2009), and 3) disorder incurred functional and structural brain changes are correlated across the source factors of modalities. A joint analysis was applied to FNC and GMD using a data fusion approach called multi-set canonical correlation analysis + joint independent component analysis (mCCA+jICA) (Sui et al 2010; Sui et al 2012b). We expected that the analysis which incorporates FNC and brain structure would reveal changes specific to BD or MDD, and that the abnormalities defined using this approach ultimately may served as potential diagnostic biomarkers with the potential to discriminate these two mood disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Different from the multi-modal techniques, multivariate but single-modal techniques such as scaled subprofile modeling (SSM) can only identify the uncorrelated sources based on single modal imaging data. MCCA and jICA have been validated and applied to identify the structural and functional abnormalities in the brain patterns of patients with schizophrenia (Sui et al, 2011, Sui et al, 2012b). The results showed that mCCA and jICA method is effective to find the function-structure correlation via the strong connection between joint components of the two modalities (Sui et al, 2011).…”
Section: Introductionmentioning
confidence: 99%